Incidence and prevalence of organ toxicities in patients suffering from clear cell renal carcinoma treated with sunitinib and its impact on survival: a reference cancer center experience - Sałek-Zań, Agata; Püsküllüoğlu, Mirosława; Jaworska, Justyna; Pietruszka, Agnieszka; Lompart, Joanna; Ziobro, Marek; Banaś, Tomasz (Frontiers in Oncology, 2025)
IntroductionTyrosine kinase inhibitors (TKIs) are the standard treatment options for advanced clear cell renal cell carcinoma (ccRCC), but their toxicities can hinder optimal dosing, affecting clinical outcomes.Material and methodsA retrospective analysis of 96 patients treated with first-line line sunitinib at the National Research Institute of Oncology, Branch Kraków, Poland was conducted to assess the incidence and prevalence of organ toxicities in ccRCC and their impact on overall survival (OS).ResultsThe study included 96 patients. The median number of treatment cycles was 11 (IQR: 19), and the median duration was 63 weeks (IQR: 95). The most common toxicities were gastrointestinal (76.0%), fatigue (61.5%), and cardiovascular (49.0%), with 81.3% of patients experiencing multi-organ toxicity. Dose delays occurred in 37 patients (38.5%), mainly due to gastrointestinal (38.5%) and cardiovascular toxicity (21.9%). Dose reductions were required in 64 patients (66.7%), primarily for gastrointestinal (39.6%) and cardiovascular (16.7%) complications. Cardiotoxicity (p=0.017) correlated with improved OS. No OS differences were observed in enterotoxicity, hematologic, endocrine, dermatologic, or renal toxicity. Patients requiring dose reduction due to cardiotoxicity (p=0.012), hematologic toxicity (p=0.004) or gastrointestinal toxicity (p=0.004) had better survival than those without modifications. Patients requiring dose reduction due to any cause had better OS than those maintaining the initial dose. The timing or frequency of dose reductions had no significant impact.ConclusionsCardiotoxicity, gastrointestinal and hematologic toxicities requiring dose reduction were associated with improved survival, suggesting these toxicities may reflect treatment efficacy. The findings emphasize the need to balance toxicity and treatment continuity.